Engineering rice with lower grain arsenic. Issue 10 (25th March 2018) - Deng, Fenglin; Yamaji, Naoki; Ma, Jian Feng; Lee, Sang‐Kyu; Jeon, Jong‐Seong; Martinoia, Enrico; Lee, Youngsook; Song, Won‐Yong
Summary: Arsenic (As) is a poisonous element that causes severe skin lesions and cancer in humans. Rice ( Oryza sativa L.) is a major dietary source of As in humans who consume this cereal as a staple food. We hypothesized that increasing As vacuolar sequestration would inhibit its translocation into the grain and reduce the amount of As entering the food chain. We developed transgenic rice plants expressing two different vacuolar As sequestration genes, ScYCF1 and OsABCC1, under the control of the RCc3 promoter in the root cortical and internode phloem cells, along with a bacterial γ‐glutamylcysteine synthetase driven by the maize UBI promoter. The transgenic rice plants exhibited reduced root‐to‐shoot and internode‐to‐grain As translocation, resulting in a 70% reduction in As accumulation in the brown rice without jeopardizing agronomic traits. This technology could be used to reduce As intake, particularly in populations of South East Asia suffering from As toxicity and thereby improve human health.